Virtual Private Network for Data and Information Communication Security:Testing on Zyxel USG 2200 Router - Nurwahidah Jamal; Ihsan Ihsan; Kety Lulu Agustin; Andi Yasir Amsal; Farida Farida; Mariatul Kiptiah (ZETROEM, 2026)
This study evaluates the efficacy and security robustness of a Remote Terminal Unit (RTU) data connection protected by a Virtual Private Network (VPN) deployed on the Zyxel USG 2200 router. The aim is to evaluate the effects of IPsec and SSL VPN implementations on network performance, particularly in terms of latency and packet loss, and to assess system resilience against cyberattacks through penetration testing. An experimental methodology was employed, involving the configuration of IPsec/SSL on the Zyxel router and VA modem, conducting packet transmission tests, and performing a security evaluation using Kali Linux tools (Hydra, NMAP, and Metasploit). The results indicate superior network performance, with latency values of 1.8 ms and 5.1 ms, and packet loss rates of 0.14% and 0.81%, signifying that the communication channel is exceptionally reliable and appropriate for real-time RTU applications. Port scanning revealed five open ports (21, 22, 53, 80, 443), but all penetration attempts were futile. Hydra faced failure due to a key-exchange mismatch; NMAP was unable to identify appropriate authentication keys despite numerous attempts, and Metasploit experienced connection issues during exploitation efforts. These findings validate that the established encryption and authentication systems offer sufficient defense against brute-force and fundamental exploitation threats. The research reveals that deploying IPsec and SSL VPN on the Zyxel USG 2200 enhances communication security while maintaining network performance. Future studies should incorporate long-term load testing and more sophisticated, multi-layered attack scenarios to achieve comprehensive security certification.